Parents' attitude towards sexual and reproductive health communication: The case of Wa West district of the Upper West Region, Ghana - Reuben Aren-enge Azie; Lawrence Bagrmwin; Mawuko Setordzi; Thomas Akuetteh Ndanu; Patience Aniteye (Elsevier, 2023)
Background: Parents' communication with their adolescents on sexual and reproductive health essentially decreases adolescent perilous sexual conduct. Available evidence supports a strong relationship between parents' attitude and their communication with adolescents on sexual and reproductive issues. Aims: This study assessed the attitude of parents towards sexual and reproductive health communication with their adolescents in the Wa West District. Methods: A community-based cross-sectional study was conducted on 420 respondents. A multistage sampling technique was used to select study respondents. Data were collected employing trained research assistants using a structured questionnaire and analysed with IBM SPSS version 25. Results: The majority (96.2%) of the respondents had a positive attitude towards adolescent sexual and reproductive health communication There was a significant relationship between the sex of respondents and attitude toward sexual and reproductive health (SRH) communication with adolescents (P < 0.03, C 1.226-54.841). Conclusion and recommendation: Parents especially females had a positive attitude towards SRH communication with their adolescents. Healthcare stakeholders need to empower female parents with SRH information to be able to fruitfully communicate with their adolescents.